E-110 Diurnal variability in the first 24/7 mobile stroke unit worldwide, a prospective observational study. (22nd July 2018) - Changal, K; Sultan-Qurraie, A; Calderon, V; Lin, E; Goins-Whitmore, J; Zaidat, O
Abstract : Background and purpose: Our mobile stroke unit (MSU) is the first 24/7 MSU worldwide. This provides a unique opportunity to report the temporal variation of its transports, types of patients treated, and therapy administered on the MSU. Methods: This was a prospective, observational study conducted over the first year of the MSU's operation. We compared different variables and metrics across the following times segments: hourly, 8 hour work shifts (morning 07:00–15:00, evening 15:01–23:00, and nocturnal 23:01–06:59), and 12 hour periods (daytime 07:00–19:00, nighttime 19:01–06:59). Results: A total of 195 patients were treated and transported by the MSU. Based on hourly segments, the majority of MSU runs occurred from 13:00 to 14:00 (10.4%). The highest rate of transport was 52.3% in the morning shift, followed by 35.8% in the evening shift, and 11.9% during the nocturnal shift. When comparing daytime to nighttime, rate of transport was 73.1% vs 26.9%, respectively. A total of 23 patients received tPA; the most frequent hourly time segment was between 13:00–14:00 (21.7%), and the least frequent period was 02:00 to 07:00 with no tPA given. Of the total tPA administered, 56.5% was given during the morning shift, 34.7% in the evening shift, and 8.6% in the nocturnal shift. Twenty (86.9%) patients received tPA during the daytime and 3 (13%) received it during nighttime runs. Only 7 patients had mechanical thrombectomy (MT), all of which were done during the daytime. Conclusions: MSU utilization varies with time of the day, with the highest rate of transport between 13:00–14:00. Higher rates of transport occur during the morning shift, compared to evening and nocturnal shifts; daytime period also has a higher rate of transport compared to nighttime period. tPA administration follows a similar trend. Staffing and utilization of a MSU can be managed more effectively if this variation is taken into account. Disclosures: K. Changal: None. A. Sultan-Qurraie: None. V. Calderon: None. E. Lin: None. J. Goins-Whitmore: None. O. Zaidat: None.